2018
DOI: 10.3390/ijerph15091890
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination Near Industrial Estate Areas in Phra Nakhon Si Ayutthaya Province, Thailand and Human Health Risk Assessment

Abstract: Industrial activity is one of the significant sources of environmental contamination with heavy metals, especially in developing countries. Flood can also lead to the distribution of toxic substances into the environment, regarding the Thailand flood in 2011 as some industrial estates are affected, leading to concern about heavy metals from industrial wastewater contamination. We aimed to measure the levels of Cd, Cr, Cu, Ni, Mn, Pb, and Zn in river and stream water, sediment, and fish collected from the area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The river is seriously polluted due to untreated wastewater. At the same time, Mingkhwan and Worakhunpiset [ 60 ] reported that heavy metal levels in water did not exceed Thailand’s surface water quality standards, except for Mn in the studied Ayutthaya Province. Chaiyara et al [ 61 ] also demonstrated that the concentrations of Cd, Cu, and Pb in the rivers were low compared to the marine standards of Chao Phraya River in Thailand and estuarine water elsewhere.…”
Section: Resultsmentioning
confidence: 96%
“…The river is seriously polluted due to untreated wastewater. At the same time, Mingkhwan and Worakhunpiset [ 60 ] reported that heavy metal levels in water did not exceed Thailand’s surface water quality standards, except for Mn in the studied Ayutthaya Province. Chaiyara et al [ 61 ] also demonstrated that the concentrations of Cd, Cu, and Pb in the rivers were low compared to the marine standards of Chao Phraya River in Thailand and estuarine water elsewhere.…”
Section: Resultsmentioning
confidence: 96%
“…Results indicated that most ions did not interfere with nitrite and total iron determination, while the most serious interferences were Hg 2+ , Cr( vi ), Cd 2+ , Cu 2+ , and Mn 2+ , Pb 2+ , Ni 2+ , and Cd 2+ on nitrite and total iron determination, respectively. These ions were present at low concentrations in surface water samples, 52–54 and our proposed system proved suitable for the dual determination of nitrite and total iron.…”
Section: Resultsmentioning
confidence: 88%
“…Mingkhwan and Worakhunpiset [ 55 ] measured the amounts of Cd, Cr, Cu, Ni, Mn, Pb, and Zn in river and stream sediment collected in industrial estates in the Uthai and Bangpa-in Districts of Phra Nakhon Si Ayutthaya Province following the 2011 floods. They found that metal levels in sediment and fish samples were within the published guidelines.…”
Section: Resultsmentioning
confidence: 99%